SDSS-IV MaNGA: probing the kinematic morphology–density relation of early-type galaxies with MaNGA - Greene, J.E.; Leauthaud, A.; Emsellem, E.; Goddard, D.; Ge, J.; Andrews, B.H.; Brinkman, J.; Brownstein, J.R.; Greco, J.; Law, D.; Lin, Y.-T.; Masters, K.L.; et al. (American Astronomical Society, 2017)
The “kinematic” morphology–density relation for early-type galaxies posits that those galaxies with low angular momentum are preferentially found in the highest-density regions of the universe. We use a large sample of galaxy groups with halo masses 1012.5 < Mhalo< 1014.5 h -1 M observed with the Mapping Nearby Galaxies at APO (MaNGA) survey to examine whether there is a correlation between local environment and rotational support that is independent of stellar mass. We find no compelling evidence for a relationship between the angular momentum content of early-type galaxies and either local overdensity or radial position within the group at fixed stellar mass.